2019
DOI: 10.1186/s13229-019-0256-6
|View full text |Cite
|
Sign up to set email alerts
|

Lower circulating endocannabinoid levels in children with autism spectrum disorder

Abstract: BackgroundThe endocannabinoid system (ECS) is a major regulator of synaptic plasticity and neuromodulation. Alterations of the ECS have been demonstrated in several animal models of autism spectrum disorder (ASD). In some of these models, activating the ECS rescued the social deficits. Evidence for dysregulations of the ECS in human ASD are emerging, but comprehensive assessments and correlations with disease characteristics have not been reported yet.MethodsSerum levels of the main endocannabinoids, N-arachid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 52 publications
8
93
1
6
Order By: Relevance
“…To date, there were only two human evidence about the eCBs levels in ASD children's blood sample [11,12], and their ndings that lower concentrations of AEA, PEA and OEA in autistic children were consistent with ours. Noteworthily, this is the rst time that we found circulating 2-AG levels were reduced in autistic children.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To date, there were only two human evidence about the eCBs levels in ASD children's blood sample [11,12], and their ndings that lower concentrations of AEA, PEA and OEA in autistic children were consistent with ours. Noteworthily, this is the rst time that we found circulating 2-AG levels were reduced in autistic children.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the dysregulation of eCB system has been documented in several neuropsychological and neurodevelopmental diseases, including ASD. Two case-control studies found decreased circulating levels of AEA, PEA and OEA in ASD children compared with their matched healthy children [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study pointed out that children afflicted by ASD have significantly reduced circulating levels of the main ECs [81], suggesting an important role of these compounds in the early stages of the disease.…”
Section: Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
“…109 Additionally, children with ASD have been found to have lower peripheral endocannabinoid levels. 110,111 Therefore, dysregulation of the endocannabinoid system may play an important role in ASD pathophysiology and may represent a target for pharmacological intervention. 112 Four uncontrolled case-series, including 60, 188, 53, and 18 children with ASD and severe behavioral problems, reported high tolerability and efficacy of artisanal CBD-rich cannabis strains.…”
Section: Medical Cannabis For Children With Autism Spectrum Disordermentioning
confidence: 99%